Built-environment attributes associated with refugee children’s physical activity: a narrative review and research agenda - Chen, Siqi; Carver, Alison; Sugiyama, Takemi; Knöll, Martin (Conflict and health, 2021)
Research has identified built environmental attributes associated with children’s physical activity (PA); however, less is known for environmental correlates of refugee children’s PA. This narrative review summarised the current evidence of associations between built environment attributes and refugee children’s PA. Six databases were searched with three sets of terms related to exposure (built environment); outcome (PA); and target population (refugee children aged 6–12 years). Eight studies (one quantitative; seven qualitative) met the inclusion criteria. Key PA barriers were limited play space and lack of neighbourhood safety. Design of refugee facilities and surrounding environments should provide better access to formal, informal and safe spaces for children’s play.